Implementasi Metode Weighted Moving Average (WMA) Pada Prediksi Harga Bahan Pokok - Ustadatin, Fina; Muqtadir, Asfan; Arifia, Amaludin (Komputika : Jurnal Sistem Komputer, 2023)
Staples are goods or commodities that are needed routinely in everyday life. Staples have an important role in meeting food needs. Availability, price, and accessibility of basic commodities can affect people's welfare. Prices of basic commodities tend to experience price volatility. This makes people uneasy and will affect the level of purchase of each staple. The purpose of this research is to predict the price of staple goods in the Tuban district market, East Java. The method used in this study is the Weighted Moving Average (WMA), to predict the price of materials using data on prices of staple foods that existed previously. This method is used in order to obtain accurate forecasting results. The Weighted Moving Average method is suitable for predicting the price of basic commodities, because it is able to provide predictions using existing data, namely previous data and can future prices. The results of this study are that the highest MAPE value is 0.3 for the staple ingredient premium rice, and the lowest MAPE value is 5.3 for the staple ingredient red chili. Keywords – Basic commodities; Forecasting; Weighted Moving Average.